SPAIN AND THE RESPONSIBILITY TO PROTECT: AN ACTIVE COMMITMENT - Vázquez Rodríguez, Beatriz (Journal of the Spanish Institute for Strategic Studies, 2018)
spain showed its commitment to the idea of the responsibility to protect from the very start of discussions at the United nations, and has since proven it in statements on the subject, at both the general assembly and the security council, in interactive dialogues on thematic resolutions and situations of armed confl ict that have given rise to the notion being invoked. one of spain’s priorities as a non-permanent member of the security council for the biennium 2015-2016 is to push for the eff ective implementation of the responsibility to protect and for the introduction of limits on the use of veto in situations of serious and massive violations of human rights. spain has also participated very actively in specifi c initiatives for the promotion of the concept as a member of the group of friends of the responsibility to protect and as a member state of the global network of responsibility to protect focal points. its commitment to the responsibility to protect at the domestic level can also be seen in the inclusion of this concept in spain’s external action strategy documents.